Rust (Hemileia vastatrix) response to climatic conditions and fungicide applications in shade-grown coffee (Coffea arabica) - Calero Ocón, Isidro (2024)
Coffee leaf rust (Hemileia vastatrix) was first reported in 1869 on a plantation on the island of Sri Lanka, Asia, and has since spread to all coffee-growing regions far from its center of origin. The coexistence between the coffee plant, primarily Coffea arabica, and the fungus Hemileia vastatrix leads to coevolution, which manifests in significant genetic variability in the plant’s resistance to the disease and the fungus’s virulence towards the plant (Avelino and Rivas, 2013). The trophic relationships between the fungus and the host are influenced by soil moisture, fruit load, genetic resistance, precipitation, relative humidity, and temperature; these are the main factors affecting plant colonization (Filho and Astorga, 2015). In this study, the behavior of H. vastatrix was recorded through sampling to describe the relationship between disease incidence and environmental conditions, such as precipitation, temperature, and relative humidity, over an 18-month period at the Santa Lucía Experimental Farm (FESL) in Heredia, Costa Rica. The main findings demonstrated that the use of triazole fungicides and copper hydroxide can maintain disease incidence below 7%, despite contributions to its development from precipitation and increased temperatures, but not from increased relative humidity. Proper management of coffee leaf rust and the presence of shade can help reduce the incidence of the disease in the coffee plantation at FESL.